2015
DOI: 10.1007/s13213-015-1084-3
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic analysis of the bacterial microbiota linked to the traditional Algerian date product “Btana”

Abstract: In this study, using high throughput Bpyrosequencing,ŵ e highlighted the bacterial diversity of the traditional Algerian date product BBtana^that is produced in southern Algeria using both direct (DBM) and indirect (UBM) methods. Metagenomic analysis yielded a total of 103,379 reads, with a 606 total operational taxonomic units (OTUs) detected. Firmicutes represented 84.79 % of the total pyrosequencing reads. Phylogenetic analysis revealed that the Bacillales represented 90.20 % ± 15.12 % of the total reads. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…To overcome this, population in southern Algeria transform dates to a traditional fermented product called Btana. Our previous study confirmed that Btana is an interesting method that prevents date spoilage for a period up to 2 years (Abekhti 2015). This product is manufactured according to two methods both inspired by traditional knowledge and have been thoroughly described in our previous study (Abekhti et al 2013).…”
Section: Introductionsupporting
confidence: 54%
“…To overcome this, population in southern Algeria transform dates to a traditional fermented product called Btana. Our previous study confirmed that Btana is an interesting method that prevents date spoilage for a period up to 2 years (Abekhti 2015). This product is manufactured according to two methods both inspired by traditional knowledge and have been thoroughly described in our previous study (Abekhti et al 2013).…”
Section: Introductionsupporting
confidence: 54%
“…The devastating impact of mycotoxins on the immune system of both adults and children is of major public health concern, while newborns are more vulnerable to mycotoxins than adults due to their smaller body weight and less acidic stomach [104]. Abass et al (2013) examined the most common species of fungi in six different date palm cultivars in Iraq, including Um Al-Dihin, Shwaythee, Breem, Barhi, Hilawi, and Al-Sayer.…”
Section: Microbiological Contamination Of Datesmentioning
confidence: 99%
“…On the extracted DNA, PCR targeting tcdA and tcdB genes was performed using primers reported by Kouhsari et al, 2019 [30]. Then, PCR targeting 16S rDNA was performed according to the protocol explained by Abdelkader et al (2021) [31]. The length of the fragment is 1500 bp, and the universal primers are 16Sr (TAC-GGT-TAC-CTT-GTT-ACG-AC) and 16Sf (GAG-TTT-GAT-CMT-GGC-TCA-G).…”
Section: Confirmation C Difficile Isolates and Toxin Gene Detectionmentioning
confidence: 99%